Assessment of reproductive performance and abortion occurrence of boer goats as influenced by farm systems and feeding practices - A. H., Norhazirah; Nulit, R.; Shohaimi, S.; Shikh Maidin, M. (Malaysian Society of Animal Production, 2016)
The objective of this study was to evaluate the effect of farm systems (intensive and semi-intensive) and feeding practices on reproductive performance (kidding rate and abortion occurrence) of female Boer goats in Peninsular Malaysia. By using a survey-purposive sampling approach, a total of 212 goat farms were surveyed and 123 farms rearing Boer goats either in intensive or semi-intensive farm system with at least of a year of operation were included in the analysis. Data on feeding practices were also gathered. In both farm systems, majority of the goat producers fed their goats twice a day and about half of them (48.6%) provided feed supplement to the pregnant goat. This feeding practice was mentioned as a method to improve the kidding rate. However, no significant different was found between the two farm systems in kidding rate (P>0.05: intensive 1.19 ± 0.09; semi-intensive 1.10 ± 0.07). In addition, the abortion incidence was rare, particularly in early and late pregnancy in intensive and semi-intensive farm systems (p>0.05; X 2 = 7.57 and 2.21, respectively). In conclusion, the rearing Boer female goats either in intensive or semi-intensive farm systems does not affect their kidding rate and abortion frequency.